2023
DOI: 10.3389/fmed.2022.1099107
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive techniques to access in vivo the skin microcirculation in patients

Abstract: The microcirculation is composed of blood vessels with mean internal diameter smaller than 100 μm. This structure is responsible for survival of cells and in the last 50 years its study has become increasingly interesting because it often participates in the pathophysiology of several diseases or can determine better or worse prognosis for them. Due to the growing importance of knowing more about the microcirculation, several techniques have been developed and now it is possible to study its structure or funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…While there have been studies that have demonstrated significant structural and cellular compatibility between pigs and humans in various organs, such as the liver [32] and those of the cardiovascular system [33], the compatibility of the microvasculature of the brain in pigs, which was the focus of our investigation, requires more comprehensive examination. Although laser Doppler flowmetry (LDF) is an established and commercially available technique [34], it cannot measure the blood flow in the human brain non-invasively. Diffuse correlation spectroscopy (DCS) is a novel technique that measures average microvascular blood flow in tissue volumes [35].…”
Section: Discussionmentioning
confidence: 99%
“…While there have been studies that have demonstrated significant structural and cellular compatibility between pigs and humans in various organs, such as the liver [32] and those of the cardiovascular system [33], the compatibility of the microvasculature of the brain in pigs, which was the focus of our investigation, requires more comprehensive examination. Although laser Doppler flowmetry (LDF) is an established and commercially available technique [34], it cannot measure the blood flow in the human brain non-invasively. Diffuse correlation spectroscopy (DCS) is a novel technique that measures average microvascular blood flow in tissue volumes [35].…”
Section: Discussionmentioning
confidence: 99%